Atypical Cartilaginous Tumors: Trends in Management. (16th December 2021) - Wells, Matthew E.; Childs, Benjamin R.; Eckhoff, Michael D.; Rajani, Rajiv; Potter, Benjamin K.; Polfer, Elizabeth M.
Abstract : Introduction: Chondrosarcomas are the most common primary bone malignancy in adults within the United States. Low-grade chondrosarcomas of the long bones, now referred to as atypical cartilaginous tumors (ACTs), have undergone considerable changes in recommended management over the past 20 years, although controversy remains. Diagnostic needle biopsy is recommended only in ambiguous lesions that cannot be clinically diagnosed with a multidisciplinary team. Local excision is preferred due to better functional and equivalent oncologic outcomes. We sought to determine whether these changes are reflected in reported management of ACTs. Methods: The National Cancer Database (NCDB) 2004 to 2016 was queried for ACTs of the long bones. Reported patient demographics and tumor clinicopathologic findings were extracted and compared between patients who underwent local excision versus wide resection. Results: We identified 1174 ACT patients in the NCDB. Of these, 586 underwent local excision and 588 underwent wide resection. No significant differences were found in patient demographics. No significant change was found in the reported percentage of diagnostic biopsies or wide resections performed over time. After multivariate regression, the single greatest predictor of performing wide resection on an ACTs was presenting tumor size. Discussion: Evaluation of the NCDB demonstrated that despite changes in the recommended management of ACTs, there has not been a significant change in surgical treatment over time. Surgeons have been performing diagnostic biopsies and wide resections at similar to historical rates. Persistency of these practices may be due to presenting tumor size, complex anatomic location, uncertainty of underlying tumor grade, or patient choice as part of clinical shared decision making. The authors anticipate that the rate of biopsies and wide resections performed will decrease over time as a result of improvements in advanced imaging and the implementation of recently updated clinical practice guidelines.